The reconstruction of late quaternary vegetation and climatic patterns on the Cape West Coast, using a charcoal sequence from Elands Bay Cave - Allsopp, Janet Christine Natalie (Department of Biological Sciences, 2016)
Bibliography: pages 118-133.